2007
DOI: 10.1109/leos.2007.4382355
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Dielectric Response Sensitivity to Protein Oxidation State

Abstract: Previously we have shown that the terahertz dielectric response is sensitive to the oxidation state for cytochrome c (CytC) films. Here we discuss the origin of this sensitivity through hydration dependent measurements on films, solution phase measurements as a function of temperature and normal mode calculations as a function of hydration. We find that the hydration dependence of the terahertz response rapidly approaches its fully solvated value for ferri CytC, whereas for ferro CytC the effect of added water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This suggested that water content and lipid concentration might lead to strong changes in the terahertz reflection. Nevertheless, a number of studies have imaged biologic samples that were fixed in formalin, dehydrated, and paraffin embedded for histopathologic examination and still found contrast between tumor and the surrounding normal tissue [7][8][9][10][11][12][13] suggesting that in addition to lipid changes, other factors such as increased cell density or the presence of certain proteins may also be responsible for contrast [16].…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that water content and lipid concentration might lead to strong changes in the terahertz reflection. Nevertheless, a number of studies have imaged biologic samples that were fixed in formalin, dehydrated, and paraffin embedded for histopathologic examination and still found contrast between tumor and the surrounding normal tissue [7][8][9][10][11][12][13] suggesting that in addition to lipid changes, other factors such as increased cell density or the presence of certain proteins may also be responsible for contrast [16].…”
Section: Introductionmentioning
confidence: 99%